Lexical coincidences between Argentina and Peru. preliminary study - Portilla Durand, Luisa (2011)
This lexicographical survey is based on a sample taken upon reviewing in the 2001 22nd edition of the Diccionario de la Real Academia Española (DRAE) 1700 headwords bearing the mark Argentina in one or more meanings. Even though this is a preliminary study, it spotlights the lexical similarity in the Spanish spoken in Argentina and Peru. This similarity is noticeable not only in the handling of expressions typical to general, supranational Spanish, but also in the treatment of expressions shared exclusively by Argentina and Peru and in the usage in Peru of Argentinian expressions yet to be recorded in the DRAE with the additional label Perú. So besides demonstrating the remarkable lexical coincidence between the two countries, some amendments are put forward for a number of headwords, either by attaching the label Perú or by correcting some meanings or adding new meanings.